Case Report: Morphologic and Functional Characteristics of Intestinal Mucosa in a Child With Short Bowel Syndrome After Treatment With Teduglutide: Evidence in Favor of GLP-2 Analog Safety - Falco, Enrico Costantino; Lezo, Antonella; Calvo, Pierluigi; Rigazio, Caterina; Opramolla, Anna; Verdun, Ludovica; Cenacchi, Giovanna; Pellegrini, Marianna; Spada, Marco; Canavese, Gabriella (Frontiers in Nutrition, 2022)
Teduglutide is a GLP-2 analogue employed in patients with Short Bowel Syndrome to reduce the need of parenteral nutrition in these patients, by virtue of its functional effects on enteric function. Experimental studies reported that the stimulating action of GLP-2 on epithelial turnover implies the potential development of dysplastic and neoplastic lesion. However, clinical trials could not detect preneoplastic lesions on histologic material, and in a recent pilot study the occurrence of polyps was similar before and after treatment and included only low-grade dysplastic lesions. Another clue in GLP-2 function in stimulating mucosal restore is its enhancement through cooperation with EGF. In this study, we analysed gastroscopy and colonoscopy samplings from a child successfully weaned off parenteral nutrition with teduglutide. Villous and crypt structure was regular both in duodenal and colonic samplings; in properly oriented villi, villus/crypt ratio was regular. Absorptive epithelium demonstrated a regular morphology. No atypia was detected in enterocytes, along epithelial structures. At the ultrastructural analysis, only a few enterocytes with vacuolized cytoplasm were observed. S-phase marker Ki67 stained nuclei in the transitional amplifying zone, while nuclei stained by the cell cycle regulatory proteins p21 and p27 were placed in the differentiated epithelium of the duodenal villi and colonic crypts, as in the control cases, and the counts of enterocytes immunostained with the same antisera, evaluated with image analysis software, were in the range of control cases. The ratio of the number of EGFR signals / the number of CEP7 signals was < 2. The findings available from this single patient are consistent with good preservation of functional capability of intestinal epithelium after treatment with GLP-2, given the histologic and ultrastructural features of enterocytes. On the other hand, findings from cell cycle regulatory proteins immunolocalization and quantitative analysis show that cell renewal machinery in our case is comparable to control cases. The gene of the receptor EGF-R is regularly expressed in enteric epithelium of our case. Morphologic and functional data from our patient improve evidence in favor of the safety of GLP-2 employ in short bowel syndrome.